Environmental factors of food literacy in Australian high schools: views of home economics teachers. (14th August 2016) - Ronto, Rimante; Ball, Lauren; Pendergast, Donna; Harris, Neil
Abstract: This study set out to examine environmental factors impacting on the food literacy of adolescents. It utilized data from a nation‐wide survey of home economics teachers regarding their experience of food literacy education in Australian high schools. Content analysis and the ANGELO framework were applied to analyse free‐text comments from 78 of the respondents that were collected as part of a more extensive data set. The analysis of environmental factors revealed three enablers and ten barriers that could influence food literacy education delivered by high schools in Australia. High schools are well positioned to improve adolescents' food literacy through a comprehensive, hands‐on approach in home economics. However, many environmental barriers were reported that could influence food literacy education in Australian high schools such as: lack of teaching materials and facilities, and human resources; the perceived inadequacy of the Australian school curriculum; non‐supportive school canteens; and negative role modelling. This study points to the need to eliminate or reduce these environmental barriers impacting on the capacity for effective food literacy education in high schools to help adolescents increase their food literacy and thereby support them in making informed food choices.